Comparison of velopharyngeal morphology of two palatoplasty techniques in patients with hard and soft cleft palate - Fan, Xiaofen; Liu, Weilong; Nie, Jiancun; Chen, Xiaoxuan; Dong, Yingchun; Lu, Yong (Frontiers in Surgery, 2023)
Purpose: The study aims to compare the velopharyngeal morphology of hard and soft cleft palate (HSCP) patients after Furlow and Sommerlad palatoplasty. Patients and methods: A total of 51 patients (20 cases in Furlow palatoplasty group, 16 cases in Sommerlad palatoplasty group and 15 normal children in the control group) were included in our study. Velopharyngeal function and speech outcomes of patients with HSCP who had either Furlow palatoplasty or Sommerlad palatoplasty for cleft palate repair were evaluated by perceptual speech assessment (PSA), lateral cephalometric radiographs and nasopharyngoscopy. Skeletal measurements including cranial base, cervical vertebrae, posterior nasal spine in the pharyngeal triangle, velar length, pharyngeal depth, and the adequate ratio of velar length to pharyngeal depth were analyzed. Results: Velopharyngeal closure (VPC) rate in Furlow palatoplasty group accounted for 90%, while that in Sommerlad palatoplasty group was 81.3%. PSA of the former group was significantly better than that of the latter group (P<0.05). Furthermore, the velar length, Adequate ratio and velopharyngeal structure were comparable between the Furlow palatoplasty group and control group (P>0.05), whereas Sommerlad palatoplasty group had a shorter velar length and a less Adequate ratio compared to Furlow palatoplasty group and control group (P<0.05). And the point U of Sommerlad palatoplasty group in the pharyngeal triangle was higher versus the other two groups. Meanwhile, the coordinate of point ANS on the x-axis in Furlow palatoplasty group and Sommerlad palatoplasty group was inferior to that in the control group (P<0.05). Conclusions: In the treatment modality of patients with HSCP, both Furlow palatoplasty and Sommerlad palatoplasty seem to be effective, whereas Furlow palatoplasty appears to have better velopharyngeal morphology and speech outcomes.